Technological trends in legal practice - Serebro, Mykhailo V.; Серебро, Михайло Володимирович; Серебро, М. В. (Одеса : Видавництво «Юридика», 2023)
It is noted that many examples of formation are now appearing a new image of legal practice, which is inextricably linked with access to new technological facets of a profession that can no longer perceived as a conservative and closed club. Not only legal practice, but also Legal science is undergoing similar atypical transformations, which already significant attention is paid, including at the monographic level.
Serebro Mykhailo V. Technological trends in legal practice / Mykhailo V. Serebro // Європейські орієнтири розвитку України в умовах війни та глобальних викликів ХХІ століття: синергія наукових, освітніх та технологічних рішень : у 2 т. : матеріали Міжнар. наук.- практ. конф. (м. Одеса, 19 травня 2023 р.) / за заг. ред. С. В. Ківалова. – Одеса : Видавництво «Юридика», 2023. – Т. 1. – С. 72-74.
Keywords: іndustry 4.0.; fourth industrial revolution; legal practice; індустрія 4.0.; четверта промислова революція; юридична практика; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::TECHNOLOGY